Nuclear N-WASP Induces Actin Polymerization in the Nucleus with Cortactin as an Essential Factor - Xin Jiang; Purusottam Mohapatra; Maria Rossing; Wenqian Zheng; Olga Zbodakova; Jayashree Vijay Thatte; Claus Storgaard Sørensen; Thu Han Le Phan; Cord Brakebusch (Cells)
Nuclear actin polymerization was reported to control different nuclear processes, but its regulation is poorly understood. Here, we show that N-WASP can trigger the formation of nuclear N-WASP/F-actin nodules. While a cancer hotspot mutant of N-WASP lacking the VCA domain (V418fs) had a dominant negative function on nuclear F-actin, an even shorter truncation mutant found in melanoma (R128*) strongly promoted nuclear actin polymerization. Nuclear localization of N-WASP was not regulated by the cell cycle and increasing nuclear F-actin formation by N-WASP had no obvious influence on replication. However, nuclear N-WASP/F-actin nodules colocalized partially with RNA Pol II clusters. N-WASP-dependent actin polymerization promoted the maturation of RNA Pol II clusters, with the short truncation mutant R128* unexpectedly showing the strongest effect. Nuclear N-WASP nodules including V418fs colocalized with WIP and cortactin. Importantly, cortactin binding was essential but not sufficient for F-actin formation, while WIP binding was required for actin polymerization by R128*. These data reveal a cortactin-dependent role for N-WASP in the regulation of nuclear F-actin and indicate contrasting nuclear effects for N-WASP mutants found in cancer.